2010
DOI: 10.1152/ajprenal.00124.2009
|View full text |Cite
|
Sign up to set email alerts
|

ERK5 activation enhances mesangial cell viability and collagen matrix accumulation in rat progressive glomerulonephritis

Abstract: The mitogen-activated protein kinase (MAPK) cascade plays an important role in the regulation of various cellular functions in glomerulonephritis (GN). Here, we investigated whether extracellular signal-regulated kinase 5 (ERK5), a member of the MAPK family, is involved in the pathogenesis of chronic mesangioproliferative GN, using a rat model induced by uninephrectomy and anti-Thy-1 antibody injection. Immunostaining of kidneys obtained at different time points revealed that phospho-ERK5 was weakly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Furthermore, the transfection of ERK5-specific small interfering RNA results in a significant decrease in ANG-II-induced soluble collagen secretion (Urushihara et al 2010), thus suggesting that ERK5 also mediates the effect of TGF-β and Ang II on mesangial-derived ECM expansion. In addition, in human mesangial cells, mechanical stretch activates p38 MAP kinase, which independently induces TGF-β1 and fibronectin.…”
Section: Effect Of Tgf-β On Mesangial Cellsmentioning
confidence: 99%
“…Furthermore, the transfection of ERK5-specific small interfering RNA results in a significant decrease in ANG-II-induced soluble collagen secretion (Urushihara et al 2010), thus suggesting that ERK5 also mediates the effect of TGF-β and Ang II on mesangial-derived ECM expansion. In addition, in human mesangial cells, mechanical stretch activates p38 MAP kinase, which independently induces TGF-β1 and fibronectin.…”
Section: Effect Of Tgf-β On Mesangial Cellsmentioning
confidence: 99%
“…Previous studies revealed that the overload of glomerular filtration increases cellular reactive oxygen species (ROS), and that ROS up-regulate cell proliferation and ECM expression in mesangial cells. 19,20) In this study, SKT suppressed both glomerular hypercellularity and ECM accumulation, together with recovery of tissue SOD-like activity, which is recognized as a ROS scavenger. Therefore, it is suspected that the antioxidative effect was one of the mechanisms of SKT treatment in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…MCs were serum-starved for 48 hours in serum-free RPMI 1640 medium, prior to stimulation with H 2 O 2 and/or Ang II in the presence or absence of reagents. Ang II-induced ERK5 phosphorylation in MCs was blocked by the pretreatment with ARB but not DPI, indicating that Ang II-induced ERK5 phosphorylation was mediated by the Ang II type 1 receptor and not by the Ang IIinduced NAD(P)H oxidase-dependent ROS production (Urushihara et al, 2010). Furthermore, the costimulation of MCs with Ang II and H 2 O 2 resulted in a synergistic increase in ERK5 phosphorylation, compared to the stimulation of MCs with either Ang II or H 2 O 2 (Urushihara et al, 2010).…”
Section: Mapk In Glomerular Cellsmentioning
confidence: 91%
“…Ang II-induced ERK5 phosphorylation in MCs was blocked by the pretreatment with ARB but not DPI, indicating that Ang II-induced ERK5 phosphorylation was mediated by the Ang II type 1 receptor and not by the Ang IIinduced NAD(P)H oxidase-dependent ROS production (Urushihara et al, 2010). Furthermore, the costimulation of MCs with Ang II and H 2 O 2 resulted in a synergistic increase in ERK5 phosphorylation, compared to the stimulation of MCs with either Ang II or H 2 O 2 (Urushihara et al, 2010). These findings suggest that Ang II directly induces ERK5 phosphorylation via NADPH in an oxidase-independent manner, and that ROS and Ang II could each induce ERK5 phosphorylation in MCs through different signaling pathways.…”
Section: Mapk In Glomerular Cellsmentioning
confidence: 91%